Post-exhibition practices in the Age of Asymmetry, for an aesthetics of eerie - Di Rosa, Vincenzo (Scenari, 2021)
How can the constitutive anthropocentrism of exhibition spaces be undermined? How can we suggest a spectatorial model that offers a different relationship with non-human entities? The thesis that this essay aims to support is that the possibility of a posthuman art is rooted in a rethinking of the “exhibitionary complex” that favors a different relationship with otherness. This choice moves from the conviction that contemporary exhibitions are not just acts of presentation, but apparatus, which direct our gaze by conveying precise visions of the world. The importance and weight given to the exhibitions indicate that the “alliance” between posthuman positions and artistic practices involves an afterthought of exposures strategies. Starting from a reconsideration of subjectivity, as proposed by Roberto Marchesini and Rosi Braidotti, this essay aims to underline how some artists have developed a kind of relationality in line with the “post-human condition”. In particular, the analysis focuses on the project created by Pierre Huyghe in the summer of 2017, titled After ALife Ahead and presented at the fifth edition of Skulptur Projekte in Münster. The French artist’s work is related to the concept of eerie developed by Mark Fisher: a particular kind of aesthetic experience that forces us to come face to face with an elusive and unknowable dimension, which exists regardless of us, and despite us.